Physical activity and psychosomatic status in patients with Behcet's disease during coronavirus disease pandemic - Yentur, Songul Baglan; Bilek, Furkan; Koca, Suleyman Serdar (Aves, 2022)
Objective: The aim of this study is to examine the changes in physical activity level, fatigue, depression, and sleep quality in patients with Behcet's disease during the COVID-19 pandemic. Methods: The study was designed as an online questionnaire applied to individuals who are being followed up with the diagnosis of Behcet's disease in the rheumatology department. Data were -collected using multiple scales including International Physical Activity Questionnaire (IPAQ), Fatigue Severity Scale (FSS), Beck Depression Inventory (BDI), Pittsburg Sleep Quality Index (PSQI), and Visual Analogue Scale ( VAS) to evaluate physical activity level, fatigue, depression, sleep quality, and pain, respectively. Results: Sixteen patients diagnosed with Behcet's disease were included in the study. No statistically significant difference was observed between the IPAQ, FSS, BDI, PSQI, and VAS assessment scores before COVID-19 and during COVID-19 period (P >.05 for all). Conclusion: Thinking of the negative effects of aggressive clinical symptoms, Behcet's disease patients should be supported in physical activity and psychosocial status.
Keywords: COVID-19; pandemic; Behcet's disease; physical activity; depression; fatigue